2012
DOI: 10.1016/j.robot.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Constraint and exploitation of redundant degrees of freedom during walking

Abstract: What kind of leg trajectories are selected during human walking? To address this question, we have analyzed leg trajectories from two points of view: constraint and exploitation of redundant degrees of freedom. First, we computed the optimal leg swing trajectories for forward and backward walking that minimize energy cost for the condition of having some stretch of elastic components at the beginning of the leg swing and found that the optimal trajectories explain the characteristics of measured trajectories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These studies have not focused on the expected value of energy cost; however, the results indicate that the design of the movement trajectory is not independent of the energy cost. As noted in section 1, it has been reported that the characteristics of locomotor parameters, such as stride frequency and stride length, can also be explained well by the criterion of the minimum energy cost (Zarrugh & Radcliffe, 1978;Nishii, 2000Nishii, , 2006Nishii et al, 2012;Minetti & Alexander, 1997;Donelan et al, 2001). Although a simple 1-DOF linear musculo-skeletal model was used in our study due to the difficulty of computing the optimal trajectory, our results and the previous studies noted suggest that minimization of the energy cost would be a basic strategy in motor planning in living beings (Nishii & Taniai, 2009).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These studies have not focused on the expected value of energy cost; however, the results indicate that the design of the movement trajectory is not independent of the energy cost. As noted in section 1, it has been reported that the characteristics of locomotor parameters, such as stride frequency and stride length, can also be explained well by the criterion of the minimum energy cost (Zarrugh & Radcliffe, 1978;Nishii, 2000Nishii, , 2006Nishii et al, 2012;Minetti & Alexander, 1997;Donelan et al, 2001). Although a simple 1-DOF linear musculo-skeletal model was used in our study due to the difficulty of computing the optimal trajectory, our results and the previous studies noted suggest that minimization of the energy cost would be a basic strategy in motor planning in living beings (Nishii & Taniai, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, many studies have reported that the characteristics of legged locomotor patterns can be explained well by the minimum metabolic energy cost model (Zarrugh & Radcliffe, 1978;Nishii, 2000Nishii, , 2006Nishii, Hashizume, Kaichida, Suenaga, & Tanaka, 2012;Minetti & Alexander, 1997;Donelan, Kram, & Kuo, 2001). Saving energy costs would be an important strategy for sustaining life in organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent our analysis has shown that the joint trajectories during walking show some fluctuations for each stride, however, such fluctuations are mutually compensated each other so as to suppress the fluctuation of the toe position at some specitic moments in a stride cycle, e.g., during double support phase and at the moment when stumbling often occurs in the middle of the swing phase [3]. Such cooperative joint movements are called joint synergy, and our analysis suggested that high joint synergy is often observed at critical points to realize stable walking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our previous study have suggested that the leg swing trajectories of forward and backward walking are designed so as to minimize the energy cost under some constraints that stabilizes walking [3]. Many other previous studies also have shown the evidences that legged locomotor patterns are well optimized on energy cost [4]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…The second point is that it is unclear how the period and amplitude of the motor command from the rhythm generator are controlled independently in order to realize a target motion. Many studies on walking patterns have suggested that many locomotor parameters, such as the stance length and stride period, are optimized for each locomotion speed, depending on the energy cost (Zarrugh & Radcliffe, 1978; Minetti & Alexander, 1997; Nishii, 2000; Donelan, Kram, & Kuo, 2001; Nishii, 2006; Nishii, Hashizume, Kaichida, Suenaga, & Tanaka, 2011). These results imply that not only the period of the motor command, but also the amplitude, is precisely controlled.…”
Section: Introductionmentioning
confidence: 99%